OPTIMISASI INTERAKSI BELAJAR: MENGUPAS PENERAPAN METODE CALL ON THE NEXT SPEAKER DALAM PEMBELAJARAN AKIDAH AKHLAK - Nasrodin Nasrodin; Mahmudah Mahmudah; Nafisatur Rohmah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2023)
This study aims to determine the application of the call on the next speaker method in learning Aqidah Akhlaq and find out the supporting and inhibiting factors of the application of the call on the next speaker method in Aqidah learning. This research uses a qualitative type of research with a case study approach. Data collection is done through observation, interviews, and documentation. Data analysis techniques include data display, data reduction, and inference. To check the validity of the data, Source Trianggulation is used. The results of this study show that the application of the call on the next speaker method in Akidah akhlak subjects has been carried out in accordance with the learning stages including planning, implementation, and evaluation and there are several supporting and inhibiting factors in the application of the call on the next speaker method in learning moral creed at MTs Darur Ridwan Parangharjo Songgon Banyuwangi.